Uji Efektivitas Nutrisi Organik Air Leri dan Pupuk NPK Majemuk Terhadap Pertumbuhan dan Hasil Tanaman Baby Kailan (Brassica oleraceae var. acephala l.) Kultivar Kale F1 - Wike Tri Anggraeni; Rommy Andhika Laksono; Rika Yayu Agustini (Peneliti.net, 2021)
Kailan cultivars of kale f1 or new veg gin have heat tolerance and strong lateral branches as well as resistance to root rot disease. Increased crop production can be done by applying the right organic and inorganic fertilizers. In this study, a combination of addition of organic and inorganic fertilizers was used to increase the production of baby kailan (Brassica oleraceae var. acephala l.). The purpose of this study was to obtain a combination of leri water nutrients and compound Npk fertilizer on the growth and yield of baby kailan (Brassica oleraceae var. Acephala L.) Kale F1 cultivar.The experiment was carried out in Kembang Kuning Village, Kec. Jatiluhur Kab. Purwakarta, West Java. implementation of the experiment in June to August 2021. The experimental method that will be used is the experimental method using a single factor Randomized Block Design (RAK) with 3 replications. There were 10 treatment combinations, namely A (Nutrition of Leri Water 0 ml/lt + 150 kg/ha NPK Pearl), B (Nutrition of Leri Water 10 ml/lt + 150 kg/ha NPK Pearl), C (Nutrition of Leri Water 20 ml/ lt + 150 kg/ha NPK Pearl), D (Nutrition Water Leri 30 ml/lt + 150 kg/ha NPK Pearl), E (Nutrition Water Leri 40 ml/lt + 150 kg/ha NPK Pearl), F (Nutrition Water Leri 0 ml/lt + 300 kg/ha NPK Pearl), G (Nutrition Water Leri 10 ml/lt + 300 kg/ha NPK Pearl), H (Nutrition Water Leri 20 ml/lt + 300 kg/ha NPK Pearl), I (Nutrition of Leri Water 30 ml/lt + 300 kg/ha NPK Pearl) and J (Nutrition of Leri Water 40 ml/lt + 300 kg/ha NPK Pearl). If the analysis data with variance and F test at 5% level showed significant results, then Duncan Multiple Range Test (DMRT) was conducted at 5% level to determine the highest treatment.The results showed that there was no significant effect of the combination of organic nutrients in leri water and NPK Mutiara on all observation parameters. However, there was treatment G (Nutrient of Water Leri10 ml/lt + 300 kg/ha NPK Pearl) which gave the highest results for each parameter of observation. The results showed that there was no significant effect of the combination of organic nutrients in leri water and pearl Npk on all observed parameters. However, there was treatment G (Leri Water Nutrient 10 ml/lt + 300 kg/ha NPK Pearl) which gave the highest yield for each parameter of observation. Treatment G (Nutrition of water leri 10ml/lt + 300 kg/ha NPK Pearl) gave the highest average yield on plant height (13.36 cm), average number of leaves (7.37 pieces), average stem diameter ( 4.06 mm), average leaf area (84.83), average root length (9.71 cm), average plant fresh weight (37.78 g) and average fresh weight per plot ( 9.71 g).